2020
DOI: 10.31703/gesr.2020(v-iv).02
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Student's Academic Achievement by Flipped Classroom Model and Traditional Lecture Method

Abstract: In recent years, a new learning approach called "Flipped classrooms model" has been stated as an effective way of learning. In this study, a statistical approach for the comparison of traditional lecture method and Flipped classrooms model has been performed for the academic performance of students in 6th and 7th semesters in the subject of Psychology. The study comprised of two semesters (32 weeks). The students in the 6th semester learned by traditional lecture method while in the 7th semester, students used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The information becomes valuable when the learners actively participate in learning process. Many instructors and researchers including (Kizkapan & Bektas, 2017;Nainggolan et al, 2020) concluded that most of the teachers had moved away from the traditional learning strategy as this learning strategy proved to be ineffective for the students in present learning scenario (Saira et al, 2020). The project-based learning strategy was an important phase in the learning process.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The information becomes valuable when the learners actively participate in learning process. Many instructors and researchers including (Kizkapan & Bektas, 2017;Nainggolan et al, 2020) concluded that most of the teachers had moved away from the traditional learning strategy as this learning strategy proved to be ineffective for the students in present learning scenario (Saira et al, 2020). The project-based learning strategy was an important phase in the learning process.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The capacity of the teacher to use learning methods, practices, and techniques determines how well a learning strategy is implemented in the classroom. In the modern day, effective learning is crucial for the development of critical thinking abilities (Saira et al, 2020a). In all areas of education, it is crucial for students' skills and cognitive growth.…”
Section: Introductionmentioning
confidence: 99%
“…Education is a basic human necessity, as well as a critical component, of a country's development (Hafeez et al, 2020). The selection of appropriate and effective teaching techniques to make the learning process helpful and to promote critical thinking abilities in learners is the most essential problem in the educational process (Saira, Ajmal, & Hafeez, 2020;Senthamarai, 2018;Tavoosy & Jelveh, 2019). The instructor's method and the learners' dynamic participation in the teaching-learning process are two essential variables in developing critical thinking abilities among the students (Nelson, 2017).…”
Section: Introductionmentioning
confidence: 99%